Mutational Analysis of Anesthetic Binding Sites and Their Effects on GABAA Receptor Activation and Modulation by Positive Allosteric Modulators of the α7 Nicotinic Receptor - Pierce, Spencer R. (2023)
The positive allosteric modulators (PAMs) of the α7 nicotinic receptor N-(5-Cl-2-hydroxyphenyl)-N′-[2-Cl-5-(trifluoromethyl)phenyl]-urea (NS-1738) and (E)-3-(furan-2-yl)-N-(p-tolyl)-acrylamide (PAM-2) potentiate the α1β2γ2L GABAA receptor through interactions with the classic anesthetic binding sites located at intersubunit interfaces in the transmembrane domain of the receptor. In the present study, we employed mutational analysis to investigate in detail the involvement and contributions made by the individual intersubunit interfaces to receptor modulation by NS-1738 and PAM-2. We show that mutations to each of the anesthetic-binding intersubunit interfaces (β+/α−, α+/β−, and γ+/β−), as well as the orphan α+/γ− interface, modify receptor potentiation by NS-1738 and PAM-2. Furthermore, mutations to any single interface can fully abolish potentiation by the α7-PAMs. The findings are discussed in the context of energetic additivity and interactions between the individual binding sites.